Shape shifting in the conflict zone - Melki, Jad (2016)
The war journalist is often portrayed as a ruggedly masculine individual who survives on hard work, self-sufficiency, and heroic dedication to the truth in a stoic culture and dangerous environment. Yet, the growing number of female war journalists subtly complicates this traditional narrative. Female war reporters navigate the precariousness of the conflict zone through the strategy of shape shifting—of switching gender performances depending on the environment and the audience. This article examines the shape-shifting phenomenon in the field, relying on 72 qualitative interviews conducted with English- and Arabic-speaking female journalists who have covered various wars and conflicts in the Arab region and beyond. On one level, interviewees say that they can work in precisely the same way as their male counterparts, downplaying their femininity and accentuating their own masculine qualities. On another rather paradoxical level, women war correspondents also sometimes foreground their feminine accessibility and intuition, especially when engaging female sources and entering private spaces inaccessible to male journalists. Finally, female conflict reporters sometimes perform an exaggerated version of feminine weakness or tacitly accept sexist treatment, especially when shape shifting can save them from danger or help them circumvent obstructions.